King Lear - Shakespeare, William, 1564-1616.; Durband, Alan. (Woodbury, N.Y. : Barron's, 1986)
Presents the original text of Shakespeare's play side by side with a modern version, discusses the author and the theater of his time, and provides quizzes and other study activities.
Keywords: Shakespeare, William, -- 1564-1616 -- Outlines, syllabi, etc; Lear, -- King of England (Legendary character) -- Drama; Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Inheritance and succession -- Drama; Fathers and daughters -- Drama; Kings and rulers -- Drama; Aging parents -- Drama; Britons -- Drama; Plays; English literature -- History and criticism; Tragedies